PENGEMBANGAN E-MODUL (BAHAN AJAR) MENGGUNAKAN CANVA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SEKOLAH DASAR - Azizah, Silvia; Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the lack of use of technology in the production of teaching materials in schools. Even though there are adequate facilities for making teaching materials using technology. The reason teachers do not make the most of the existing facilities is because of a lack of time and not enough ability to design teaching materials using technology. This research aims to develop a valid, practical and effective e-module using canva in Indonesian language learning in grade IV of elementary school. This type of research uses a type of development research. The development model used is the ADDIE model which consists of five stages, namely Analyze, Design, Development, Implementation, Evaluation. The e-modules that have been designed are then validated by validators of material experts, linguists, media experts, and driving teachers using validation sheets in the form of questionnaires. The practicality of the product is carried out by filling out a questionnaire of teacher and student responses. The effectiveness test was carried out by giving pre-test and post-test questions to students. The results of this research obtained e-modules that are valid, practical, and effective to be used in the learning process. The validation results of four validators, namely material experts, linguists, media experts, and driving teachers, obtained a final result of 93% with the category